O cuidado da equipe de estratégia de saúde da família a trabalhadores rurais expostos a agrotóxicos - Machado, Letícia Martins (2012)
The objectives of this study were to understand how the work of the Family Health Strategy team is organized in relation to the care of the rural workers exposed to pesticides; describe the particularities of the rural work and workers; characterize the social demographic data of the health professionals who work at the ESF and identify the health actions done by the ESF teams in relation to the rural workers, as well as to those exposed to pesticides. It is an explorative-descriptive study of qualitative approach developed with 15 health professionals of the Family Health Strategy in the city of Nova Palma/RS. The instruments of data collection were the passive observation and the semi structured interview. To analyze the data it was applied the thematic analyzes. The results are shown in two articles. The first article is organized in two categories: particularities of the rural work and workers and the attitude of the rural workers toward the pesticides. The second article is composed by the categories: social demographic categorization of the participants of the survey; experience of the health professionals in the rural area and the professional conduct of the health professional in case of intoxication. To serve ethical precepts it was fully accomplished the 196/96 resolution. This study may contribute to the care of the rural workers exposed to pesticides so that it could be organized by the health team in a way to contemplate such specificity by the full time attention to health. Moreover, the aim of this study is to contribute to managers, health workers and researchers to their practices in studies that disclose the specificity and the aggravation resulting from activities that expose the workers to the use of pesticides. The construction of this study allowed the comprehension of the rural work dynamics, by the view of the health professionals. Giving this, it is emphasized the necessity of investment in the organization of actions related to the rural workers health in general, as well as in relation to pesticide exposition.